HEALTHY PLACES: THE RELATIONSHIP BETWEEN ARCHITECTURE AND NURSING - Mário Cardoso; Helena Presado; Tiago Nascimento (European Scientific Journal, ESJ, 2015)
Objective: To identify the contributions that the nursing profession can make to the architecture of the health spaces in order to make them the most appropriate and sustainable as possible. Methods: Systematic review of the literature. Used the Nursing & Allied Health Collection databases: Comprehensive, CINAHL Complete, Library, Information Science & Technology Abstracts; & MedicLatina. The articles were selected with the following criteria: 1. Full-text articles; 2. Peer-reviewed articles. 3. Articles published between 1994 to 2014. We selected 10 of the 117 articles presented. Results: Nurses can provide valuable contributions in accordance with its practice and holistic view of the patient that may lead to health outcomes, not only for patients and their families but also for multidisciplinary teams working in the various contexts of care such as acute care, primary care and long-term care, improving the work satisfaction and reducing the turnover. Healthy healthcare environments are associated not only with better health outcomes but also with better management of human and financial resources. Conclusions: it should be promoted a partnership and coordination between architecture and nursing, to promote healthy environments for patients and professionals, working together to eliminate architectural barriers and investing in financial and ecological sustainability of spaces. Further studies are needed to support this evidence.